Evaluating the breeding potential of yearling bulls (Progress Report) - Corah, L.; Kiracofe, G.; Bridson, V.; McKee, M.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Although this is based on only ones years’ results, it indicates that the breeding potential of yearling bulls can be determined before they are run with a cow herd. In this test one bull sired the majority of the calves and generally was the bull predetermined to be the active breeder. Results of the test suggest that a good, active, breeding yearling bull is capable of breeding more than 12 to 15 cows as is normally recommended. In our studies, one yearling bull sired up to 36 calves in a 45-day breeding season. Possible adverse effects of using a yearling bull that much are being evaluated.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Yearling bulls; Breed potential; Reproductive performance